The Curriculum of Religious Education of Schools in the Countries Around the World - Mukhsin (Asyahid Journal of Islamic and Quranic Studies (AJIQS), 2023)
Religion has many meaningful values for human being life. All of them need it although they are from communists. The communists, in fact however, need beliefs with other name outside of religion name. The study aims to find differences and similarities regarding the implementation of the religious education curriculum in schools in countries around the world. The approach of study is a qualitative-descriptive method by studying related library sources and the results of research of previous researchers from various countries, and then concluding the research data. The study concludes that religious values are eternal and universal ones for all people. The people in one country and ones in other countries are different in believing what they believe and behave. But they are same in getting meaning of religious values urgency for their life. So they desire to bring these down to their generation through education or teaching process. Many countries all over the world pay attention to this urgency. They enter religious education into schools’ curriculum that must be studied by all students of schools.  Key words: curriculum, religious education, schools’ education   Abstrak Agama mempunyai banyak nilai yang bermakna bagi kehidupan manusia. Semuanya membutuhkannya meski dari komunis. Namun kaum komunis justru membutuhkan kepercayaan dengan nama lain di luar nama agama. Penelitian ini bertujuan untuk menemukan perbedaan dan persamaan mengenai penerapan kurikulum pendidikan agama di sekolah-sekolah di negara-negara di dunia. Pendekatan penelitian yang digunakan adalah metode kualitatif-deskriptif dengan mempelajari sumber-sumber kepustakaan terkait dan hasil penelitian para peneliti terdahulu dari berbagai negara, kemudian menyimpulkan data penelitiannya. Kajian tersebut menyimpulkan bahwa nilai-nilai agama bersifat abadi dan universal bagi semua orang. Masyarakat di suatu negara dan masyarakat di negara lain berbeda dalam mempercayai apa yang mereka yakini dan berperilaku. Namun mereka sama dalam memahami urgensi nilai-nilai agama bagi kehidupan mereka. Sehingga mereka ingin mewariskannya kepada generasinya melalui proses pendidikan atau pengajaran. Banyak negara di dunia menaruh perhatian terhadap urgensi ini. Mereka memasukkan pendidikan agama ke dalam kurikulum sekolah yang wajib dipelajari oleh seluruh siswa sekolah. Kata kunci: kurikulum, pendidikan agama, pendidikan sekolah